FINANCIAL LITERACY, ACCESS TO FINANCE AND THE PROVISION OF SCHOOL RESOURCES AMONG PRIVATE SCHOOLS IN NIGERIA - Tunji S. ONAKOYA; Onoriode C. POTOKRI (Financial Studies)
This study provides empirical data to expose the role of school owners' financial literacy in the relationship between access to finance and the provision of school resources among private schools in south west Nigeria. A multistage sampling technique was adopted to determine the participants who participated as respondents in the study. Three research instruments were adopted for the study. The instruments used were the private school access to finance questionnaire, a financial literacy questionnaire, and a school resources checklist. Data collected were analysed using inferential statistics of multiple regression and mediation analysis. The findings show that access to finance significantly influences the provision of school resources among private schools. The study also found that school owners' financial literacy mediates the relationship between access to finance and the provision of school finance among private schools in south-west Nigeria. The study recommends that financial literacy courses be included in the university's curriculum for undergraduates and postgraduate students in the departments and faculties of education of various universities in Nigeria.